From protective to connective professionalism: Quo Vadis professional exclusivity?. Issue 2 (18th August 2020) - Adams, Tracey L; Kirkpatrick, Ian; Tolbert, Pamela S; Waring, Justin
Abstract: This essay is composed of commentaries from four scholars critically evaluating Noordegraaf's article 'Protective or Connective Professionalism? How Connected Professionals Can (Still) Act as Autonomous and Authoritative Experts'. All four scholars, in different ways and from their different perspectives, question the dichotomy at the heart of Noordegraaf's article, arguing that professionals have always been connective and connected, and moreover, that protective professionalism has not disappeared. They recommend more conceptual development to unpack the changing nature of connectivity and protectionism, as well as more attention to inequalities within and among professions, power, and professional agency.